A venda forçada no direito do urbanismo - Galado, Henrique Manuel Valente (2018)
Enforced sale is an innovative legal institute within the framework of urban policy instruments, namely in what concerns the intervention of Public Administration whenever owners do not comply with urban law. It represents a deprivation of private property, with effects similar to those in expropriation, although being an alternative. The private citizen is disappropriated of its goods against its will, through the payment of a price not, in any event, less than a fair compensation. The good is permanently transmitted in a public auction to the highest bidder whom also compromises to rehabilitate the property within the time limit, established by the Administration. The underlying idea is that owners do not make works, or if they do, the required work is replaced, in order to attain to the fundamental social function of the property right, thus restoring the property. Created in 2009 with the approval of the Legal Regime of Urban Rehabilitation, this legal institute has never been the subject of a proper debate. Therefore, in this dissertation there is an in-depth analysis of the enforced sale, as well as its legal nature, its legal regime and constitutional conformity. Throughout the study a comparison of the enforced sale and expropriation for public use is made, demonstrating that, in fact, both represent the same interest.